Eksistensi Warok Dan Gemblak di tengah Masyarakat Muslim Ponorogo Tahun 1960-1980 - Krismawati, Nia Ulfia; Warto, Warto; Suryani, Nunuk (Religió: Jurnal Studi Agama-agama, 2018)
Warok is a central figure in the life of Ponorogo Society. The existence, authority, and high social status became a social capital in the perpetuating of an ideology of kanuragan. The groups of Warok has believed that a woman is a source of weakness for mysticists that forces them to resist the lust and avoid a woman. Some of Warok presented a figure of gemblak as diversion of lust as well as an assistant in the various activities. The “menggemblak” behavior was considered not in accordance with religious values and norms because it leads to deviant practices. This study is aimed to analyze the existence of warok and gemblak in the social structure of Ponorogo society and how warok attempted to perpetuate gemblak tradition among the Muslim society as majority. The result showed that the strategic position, social status, and power to influence in the social structure became the social capital to socialize the practice of ablution as kanuragan ideology and it is normal. Meanwhile, the Islamic efforts in shifting the gemblak tradition were carried out through modification of Reog which is considered as an appropriate means of conveying religious values